The Association Between Psychological Capital and Self-Management Behaviors in Men with Gout: A Cross-Sectional Study in Southwest China - Wang Y; Chen Y; Qi Q; Song Y; Guo X; Ma L; Chen H (Patient Preference and Adherence)
Ying Wang,1 Yanling Chen,1 Qi Qi,2 Yuqing Song,3 Xin Guo,1 Ling Ma,1 Hong Chen4 1Department of Rheumatology and Immunology, West China Hospital of Sichuan University/West China School of Nursing, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Department of Operating Room Nursing, West China Second University Hospital, Sichuan University/West China School of Nursing, Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, Sichuan, People’s Republic of China; 3School of Nursing, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China; 4West China School of Nursing/ West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Hong Chen, West China School of Nursing/West China Hospital, Sichuan University, No. 37, Guoxue Alley, Wuhou District, Chengdu, Sichuan, 610041, People’s Republic of China, Tel +86 18980601733, Email chong@scu.edu.cnPurpose: Gout is a common, chronic inflammatory joint disease, and men are more likely to suffer from gout. Improving patient self-management behaviors is a priority in gout healthcare. Psychological capital is associated with self-management behaviors in chronic diseases and can be improved through a number of interventions. However, this topic has not been well studied in gout patients. The aim of this study was to determine the level of psychological capital among male gout patients in Southwest China and to compare differences in self-management behaviors among patients with different levels of psychological capital.Patients and Methods: This was a cross-sectional study. A total of 242 male gout patients were recruited from West China Hospital of Sichuan University, and demographic characteristics, clinical characteristics, psychological capital, and behavioral variables related to patient self-management were collected. K-Means cluster analysis was used to characterize psychological capital.Results: The total psychological capital score of the participants was 134.5 (SD = 21.3). Cluster analysis of the four dimensions of psychological capital yielded three clusters, namely, Cluster 1 (higher level, 29.8%), Cluster 2 (moderate level, 52.3%), and Cluster 3 (poor level, 17.9%). The differences in the self-management behaviors among the three clusters, the differences were statistically significant. Post hoc analyses revealed that cluster 1 scored higher on the self-Management behaviors and its four dimensions than either cluster 2 or cluster 3 (p < 0.05).Conclusion: The psychological capital of men with gout in Southwest China could be improved, and moderate and low levels of psychological capital are associated with suboptimal self-management behaviors. Healthcare providers may target gout patients with low or moderate levels of psychological capital as an intervention and take steps to improve their levels of psychological capital. These results may assist in decision-making for self-management behavioral interventions for gout patients.Keywords: self efficacy, resilience, optimism, hope, cluster analysis